Optimalisasi Layanan Inklusi di SMA N 2 Mengwi Melalui Aplikasi Profiling Siswa - Ida Ayu Agung Ekasriadi; Sumandya, I Wayan; I Wayan Edi Sanjana; I Wayan Widana (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
This Community Service aims to optimize inclusive services at SMAN 2 Mengwi through the development and implementation of a student profiling application. This application is designed to assist teachers and educators in accurately identifying the special needs of students in a comprehensive manner, enabling the provision of appropriate educational interventions according to each student's profile. The methods used include the development of a web-based application for student profiling, training teachers on how to use the application, and providing support during daily implementation. The first stage involves collecting data on students' special needs and assessing their conditions. This data is then integrated into the application, creating a comprehensive profile for each student, covering academic, social, emotional, and special needs aspects. Once the application is ready, intensive training is provided to teachers and relevant staff on how to use and leverage the application in the learning process. Support is provided to ensure smooth implementation and offer technical assistance if needed. The results of this activity show that the use of the student profiling application improves teacher efficiency in managing inclusive classrooms. Teachers can quickly access essential information about students' special needs and design more adaptive teaching strategies. Moreover, the application enhances parental involvement in supporting their children's learning process. Overall, this activity has successfully improved the quality of inclusive services at SMAN 2 Mengwi and is expected to provide a sustainable solution for managing inclusive education in schools.